Prognostic role of antibody reactivity to melanoma. - Vlock, D R; DerSimonian, R; Kirkwood, J M (The Journal of Clinical Investigation, 1986)
Antibody reactivity against cultured allogeneic melanoma Y-Mel 81:180 was studied in 43 patients who participated in an adjuvant trial for stage I and II melanoma. Serum samples were obtained at trial entry within 2 mo of definitive surgery. At the time of serum acquisition, all patients were free of disease by physical examination and routine radiologic and laboratory parameters. Serum antibody reactivity was tested for by protein A hemadsorption before and after acid dissociation and ultrafiltration of serum. We have previously shown that this technique for immune complex dissociation augments autologous antibody reactivity. Results of serum antibody reactivity were scored by an investigator blinded to the patient's clinical status. Of the 43 patients studied, 15 relapsed and 28 remained disease-free. At study entry, there were 25 stage I patients and 18 stage II patients. Breslow depth was 3.25 +/- 2.5 mm in relapse patients and 1.67 +/- 1.1 mm in disease-free patients. The presence and titer of antibody directed against melanoma in either native serum or serum dissociated from immune complexes was found to be associated with eventual relapse (P = 0.0001). When results were subgrouped by stage of disease, Breslow depth, and hypopigmentation, antibody reactivity was still correlated with eventual relapse. The incidence and titer of antibody reactivity against melanoma appears to be a new prognostic factor in predicting eventual disease recurrence.